2014
DOI: 10.1371/journal.pone.0102997
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus71 (EV71) Utilise Host microRNAs to Mediate Host Immune System Enhancing Survival during Infection

Abstract: Hand, Foot and Mouth Disease (HFMD) is a self-limiting viral disease that mainly affects infants and children. In contrast with other HFMD causing enteroviruses, Enterovirus71 (EV71) has commonly been associated with severe clinical manifestation leading to death. Currently, due to a lack in understanding of EV71 pathogenesis, there is no antiviral therapeutics for the treatment of HFMD patients. Therefore the need to better understand the mechanism of EV71 pathogenesis is warranted. We have previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…The research results of Li et al suggested that miRNA-548 regulates host antiviral response via direct targeting of IFN-λ1 [ 14 ]. Using a human colorectal adenocarcinoma cell line (HT29) based EV71 infection model, Lui et al showed that knockdown of DGCR8, an essential cofactor for microRNAs biogenesis, resulted in a reduction of EV71 replication [ 15 ]. Zhang [ 16 ] has demonstrated that miR-27a may have antiviral activity against EV71 by inhibiting EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…The research results of Li et al suggested that miRNA-548 regulates host antiviral response via direct targeting of IFN-λ1 [ 14 ]. Using a human colorectal adenocarcinoma cell line (HT29) based EV71 infection model, Lui et al showed that knockdown of DGCR8, an essential cofactor for microRNAs biogenesis, resulted in a reduction of EV71 replication [ 15 ]. Zhang [ 16 ] has demonstrated that miR-27a may have antiviral activity against EV71 by inhibiting EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of miRNAs up-regulated TLR signaling, RLR signaling, NOD signaling and type 1 IFN signaling. Moreover, microarray and qPCR analysis showed that miR-548 is a potential candidate that may participate in the inhibition of host antiviral responses during EV71 infection [ 75 ].…”
Section: 3c and 2a Proteases Of Ev71 Are The Main Antagonists Of Tmentioning
confidence: 99%
“…Now, it has been determined that these processes are one of the important strategies of pathogenic bacteria for intracellular survival [34]. Pathogens exploit hosted miRNAs to eliminate immune responses [35][36][37][38][39][40][41][42][43]. In this article, we briefly reviewed the expression and role of various miRNAs, during infection with M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate the gene expression changes and variation in cellular compositions. Several miRNAs regulate T cell differentiation and their function [43,51]. Bin et al showed that the activation pathway of the intrinsic macrophages could change regulation, through several miRNAs ( Fig.…”
Section: Introductionmentioning
confidence: 99%